The SFD opportunity of applicable in a potato improvement research - Csák, Máté; Hegedüs, Géza (Acta Agraria Kaposváriensis, 2008)
The spectral fractal dimension (SFD) is as a properties of picture come up in one couple research and method of investigation (EMOR/Egzact Qualify and Classification System, IKTA-00101/2003). However in this research don’t come on that what swing the value of SFD. We fin din the course of researc that this function the value is very sensible at the condition of recording. The aim of research deffinating that the valueout of condition which environmental condition is indifferent, and which variation can we give value- transformation rules. Accordingly we executed test the important condititon of recording (light intensity, diffuse and directional light, flare, scanning, spectral change). The results of test certify the pre- awaiting in point of vetted factor. The value of several factors changing give rise to value of SFD change which – by results of test – we can confine. We found ont he intensity-corrections equation on a approximation the other situation must more research and we think that this come on better results with wich we can decolonizing from the condition of environmental so the measurement method will simpler. The results mark that we would like applicating in the potato improvement the SFD the species genetics separate, the objective species rating deffinition, automatic analysis, qualify process inpractice apllication, so just we can make between good environmental conditions.
Keywords: spectral fractal dimension; SFD; image analysis